PREPARATION OF MEDICINAL BEVERAGES BASED ON HERBAL PLANTS AND ASSESSMENT OF THEIR SAFETY INDICATORS. (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The aim of this study is to develop herbal-based medicinal beverages using selected medicinal plants and to evaluate their safety indicators, including microbiological quality, chemical composition, and potential toxicity. The research seeks to establish safe preparation methods and ensure that the resulting beverages provide health benefits without posing risks to consumers.